α(2A)- and α(2C)-Adrenoceptors as Potential Targets for Dopamine and Dopamine Receptor Ligands - Sánchez-Soto, Marta (Mol Neurobiol, 2018)
The poor norepinephrine innervation and high density of Gi/o-coupled α(2A) and α(2C) adrenoceptors in the striatum and the dense striatal dopamine innervation have prompted the possibility that dopamine could be an effective adrenoceptor ligand. Nevertheless, the reported adrenoceptor agonistic properties of dopamine are still inconclusive. In this study, we analyzed the binding of norepinephrine, dopamine and several compounds reported as selective dopamine D(2)-like receptor ligands, such as the D(3) receptor agonist 7-OH-PIPAT and the D(4) receptor agonist RO-105824, to α(2) adrenoceptors in cortical and striatal tissue, which express α(2A) adrenoceptors and both α(2A) and α(2C) adrenoceptors, respectively. The affinity of dopamine for α(2) adrenoceptors was found to be similar to that for D(1)-like and D(2)-like receptors. Moreover, the exogenous dopamine receptor ligands also showed high affinity for α(2A) and α(2C) adrenoceptors. Their ability to activate Gi/o proteins through α(2A) and α(2C) adrenoceptors was also analyzed in transfected cells with bioluminescent resonance energy transfer techniques. The relative ligand potencies and efficacies were dependent on the Gi/o protein subtype. Furthermore, dopamine binding to α(2) adrenoceptors was functional, inducing changes in dynamic mass redistribution, adenylyl cyclase activity and ERK1/2 phosphorylation. Binding events were further studied with computer modeling of ligand docking. Docking of dopamine at α(2A) and α(2C) adrenoceptors was nearly identical to its binding to the crystallized D(3) receptor. Therefore, we provide conclusive evidence that α(2A) and α(2C) adrenoceptors are functional receptors for norepinephrine, dopamine and other previously assumed selective D(2)-like receptor ligands, which calls for revisiting previous studies with those ligands.